THE EFFECTS OF PRACTICUM PRACTICE ON TURKISH PRESERVICE EFL TEACHERS’ BELIEF SYSTEMS - Ünaldı, İhsan and Baykara, Tuba (International Online Journal of Education and Teaching, 2023)
Research related to teacher cognition has regained momentum over the years, and related problems have been studied from different perspectives. Studies concerning the belief systems of Turkish preservice teachers in the English as a foreign language (EFL) domain are existent but insufficient. This study tries to add to the existent literature by examining the changes in belief systems of Turkish EFL preservice teachers during a 14-week practicum practice. To this end, a case study was carried out at a public university in Turkey. Reflection reports of 53 preservice teachers, which were written both at the beginning and the end of the practicum practice, were analyzed using content analysis. The results revealed that certain changes in participants’ belief systems appeared during the practicum practice. The changes clustered around five main categories: the use of mother tongue in language instruction, the affective aspect of teaching, teaching mechanism, the use of technology in language instruction, and the relationship between theory and practice. We discuss the results in relation to the related literature and provide implications along with suggestions. In many countries, students enroll in a school without being given a choice and spend most of their time with teachers and administrators they have never met before. This research was carried out to analyze the opinions of students about the school and its staff, which can often be considered as the fate of students by some people. The research was carried out with 27 students, 14 female and 13 male, studying in five different secondary schools in the 2022-2023 fall semester. In this study, which was conducted with the qualitative research method, the data were collected using a semi-structured interview form prepared by the researchers. Content and descriptive analysis techniques were used in the analysis of the data. As a result of the research, it was observed that the most positive opinions of the students were towards the teachers, and the most negative opinions were related to the school administrators. It has been determined that more than half of them have negative opinions about the concept of school. Keywords: English as a foreign language, teacher education, preservice teachers, teacher cognition